Information needs of formal caregivers: A case study of children at risk care institutions / Nurul Hazimah Ab. Durahman - Nurul Hazimah , Ab. Durahman (2018)
This research presents the information needs of formal caregivers at children at risk care institutions using qualitative study by using unstructured interviews. The following research questions were addressed: (a) what are the roles and tasks of formal caregivers of children at risk?, (b) what are the characteristics of information needs of formal caregivers at children at risk institutions?, (c) what are the awareness of information by formal caregivers of children at risk?, and (d) what are the sources of information needs used by formal caregivers of children at risk?. The data collection involved seven face-to-face interviews and two focus group sessions. The data were analysed using NVivo 11 software and the general themes for the information needs of caregivers have been classified. The Leckie et al. (1996) model has been used as a model of information needs for this research. It was found that the caregivers have several roles in the institution, including guardian, counselor, and administrator with several tasks from each role including educating, parenting, supervising, counseling, and administering duties. It is transpired that the respondents’ roles require specific information needs such as children’s background, day to day information, child education, sex education, monitoring former children, disciplinary action, sport information, safety information, child reward, and Health information. It was found that there were several sources used by the caregivers when seeking information including interpersonal communication, internet sources, printed materials, statistic, television, exhibition, social media, email, memo, fax, and meetings. Hence, this study is important to identify the information needs of the caregivers at children at risk care institutions.